Diseminasi Teknologi Pembudidaya Ikan pada Kelompok Pembudidaya Ikan di Kelurahan Demang Lebar Daun - Griha Tofik Isa, Indra; Mayasari, Riana; Rahmanda Putra, Rian (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2022)
The fisheries sector is the main part of the people of South Sumatra because fish is the main material for common snack in South Sumatera such as pempek, pindang, tekwan and others. However, the availability in the market is less stable resulting in high fluctuating prices. The main problem that causes this condition to occur upstream is the process of feeding by fish farmers include “Macan Kumbang” Fish Cultivator Group. In this process there is inefficiency up to 75%. In general the “Macan Kumbang” Fish Cultivators have not been introduced with the help of technology. The priority problems faced by partners are the provision of fish feed is not timely,frequent overfeeding,pond water quality is difficult to measure,there is no fish farming waste management yet,partners have difficulty in predicting the return on capital from fish farming. So that in this activity the aim is to build IoT-based fish farming technology that is integrated with Urban Farming which can provide added value for the fish farming results of the Panther Panther fish cultivator group. The implementation method is carried out by socialization,identification of needs,tool design,making tools with assembly process,operation Testing,operational Assistance of various elementstransfer of technology through training.